PENGARUH PENERAPAN KOLKABA COMFORT THEORY DALAM MANAJEMEN ASUHAN KEPERAWATAN (ASKEP) TERHADAP KENYAMANAN PASIEN POST SECTION SESAREA (SC) DI RUMAH SAKIT IBNU SINA YARSI SUMATERA BARAT BUKITTINGGI TAHUN 2017 - Morita, Kriscillia Molly (Menara Ilmu, 2018)
The patient comfort is responsibility to provide the nursing service. The result ofpreliminary study showed that the patients experienced sense of discomfort due to the painof post SC wound. This study aims to determine the effect of the application of nursingservices based on Comfort Theory on patient Post Sectio Cesarean comfort level. Thisresearch is quantitative quasi-experimental research, non equivalent, control group onlypost test design. The research population are all nurses in the midwifery room as many as10 people taken by total sampling and post-SC patients who treated in midwifery room asmany as 32 people taken by non probability consecutive sampling. Data collection is doneby questionnaire and observation. The results showed that based on the statistical testresulted in p value of 0.001 and t value of 17.972. Compared to the fact that the value of pvalue is less than 0.05, it can be concluded that there is a difference between theintervention group and the control group or there is a significant influence on theapplication of kolkaba comfort theory to the comfort level of the post Sectio Cesareanpatient as a wholeKeywords : Nursing Management, Kolkaba Comfort Theory, nurseReference : 40 (2001-2015)